2019
DOI: 10.1016/j.gaitpost.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Objective parameters to measure (in)stability of the knee joint during gait: A review of literature

Abstract: The number of tables: 3 Highlights  Eighty-nine gait studies used objective parameters to measure knee (in)stability.  Thirty-three different objective parameters during (challenged) gait were identified.  Limited or conflicting results were reported on the validity of the parameters.  The community is urged to define a clear concept of knee stability during gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 103 publications
(199 reference statements)
0
9
0
Order By: Relevance
“…As knee joint instability in these populations is prevented by the original or reconstructed ACL, it is difficult to transfer the results on brace stabilization effects to ACLdeficient patients. Finally, we recorded 3D knee joint kinematics as these have been suggested to indicate knee joint stability (Schrijvers et al, 2019).…”
Section: Embedding Of the Results Into The Current State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As knee joint instability in these populations is prevented by the original or reconstructed ACL, it is difficult to transfer the results on brace stabilization effects to ACLdeficient patients. Finally, we recorded 3D knee joint kinematics as these have been suggested to indicate knee joint stability (Schrijvers et al, 2019).…”
Section: Embedding Of the Results Into The Current State Of Researchmentioning
confidence: 99%
“…Three-dimensional marker trajectories were filtered using a second-order Butterworth low-pass filter with a cut-off frequency of 6 Hz for the walking condition and 10 Hz for the cutting condition (Kirtley, 2006). An inverse kinematics approach using the multi-body model Dynamicus (Härtel and Hermsdorf, 2006) was used to calculate 3D knee angles as objective parameters suggested in the literature to be indicators for knee joint stability (Schrijvers et al, 2019). Based on the preprocessed data, peak joint angles (minimum and maximum), ranges of motion (RoM), joint angles at touch down (TD) and at resultant peak ground reaction force (Peak GRF) in the sagittal, frontal and transverse planes were calculated for the knee joint during the stance phases of walking and cutting.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Objectifying knee instability that patients experience during daily living still remains a challenge. 19 Laxity in the knee joint measured via different diagnostic techniques is different from instability experienced by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the evaluation of instability is based mainly on subjective self-reporting. Parameters measured with gait analysis have been studied as more objective indicators of instability; however, a recent review concluded that although many different candidates for an objective knee stability gait parameter are found in literature, all of them lack sufficient clinical evidence 13 . Here, we assessed the knee instability from one-leg-stand analysis, which we previously reported was associated with changes in morphological features of the cartilage assessed by radiography and MRI 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Gait analysis has been suggested as a potential method to quantify the information occurring during walk and especially detect abnormal movement. Measured parameters from the gait analysis have been considered as suitable objective markers of kinematic instability 13 . However, while the previous studies have been focusing on video-based approaches, the recent developments of inertial measurement units (IMU) allow to evaluate similar information using embedded sensors into wearable devices.…”
Section: Introductionmentioning
confidence: 99%